Prevalência de casos notificados de sífilis em gestante e sífilis congênita no estado de Sergipe entre 2007 e junho de 2013 - Barros, Layla Barbosa (2013)
Knowing the prevalence of reported cases of syphilis in pregnant women and congenit in the state of Sergipe between 2007 and June 2013. Methods. Analysis of cross-sectional, descriptive and retrospective component, using only secondary data from the Information System for Notifiable Diseases, Ministry of Health of Brazil. The data collected refer to the period 2007 to June 2013. It was used SPSS 17.0 for data analysis. Results. It has reported 1450 cases of syphilis in pregnant women, 47% with latent syphilis, 30% with treatment considered inadequate, 42% of partners were not treated. As for congenital syphilis cases were reported in 1371, 48.5% newborn of female, 50% of mothers received treatment, 68.9% underwent prenatal, 48% received a diagnosis at the time of delivery or curettage. Conclusion. The analysis shows that, as in nationwide, the central problem of the high prevalence of vertical transmission of syphilis is the ineffectiveness of prenatal care offered to pregnant women.